Design of proportional integral and derivative controller using particle swarm optimization technique for gimbal system - Mohd Hafiez Ahmad; Khairuddin Osman; Sharatul Izah Samsudin (Institute of Advanced Engineering and Science, 2022)
This paper presents the development of an optimal proportional, integral and derivative (PID) controller for controlling camera gimbal on unmanned aerial systems (UAV). Three optimal controller improvements are obtained using the suggested particle swarm optimization (PSO) technique. The PSO algorithm is initially built and integrated with the PID controller to control the DC motor gimbal. Before comparing the performance of a DC motor with PSO-PID with a DC motor with Zeigler-Nichols controller, the impacts of iteration numbers are explored. Finally, bode analysis was conducted to validate the stability of the proposed PSO-PID controller. Simulation is conducted within the MATLAB environment to verify the system's performance in terms of settling time, steady-state error and overshoot. The simulation results show has a longer settling time (0.91656 sec) than the Ziegler-Nichols controller (0.14316 sec) but a shorter rising time (0.091686 sec) than the Ziegler-Nichols controller (0.00094 sec). Furthermore, the overshoot was lowered from 12.941% to 0.959% as a result. As a result, the suggested PSO-PID controller technique outperforms the Ziegler-Nichols controller in terms of overshoot and rise time. Further study will investigate the integration of other optimisation methodologies such as fuzzy logic for better performance.